PENGARUH ASIMETRI INFORMASI, KECUKUPAN ANGGARAN, KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP HUBUNGAN PARTISIPASI ANGGARAN DENGAN SENJANGAN ANGGARAN (STUDI EMPIRIS PADA SATUAN KERJA PERANGKAT DAERAH KOTA DUMAI) - Yudha Kurniawan; Emrinaldi Nur DP; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Public sector was tool to measure of performance-based budgeting system which used by efficient development process and participative, and the used of performance as benchmark in the achievement of local budgets. However, the performance-based budgeting system could motivate the agent to perform budgetary slack for better future career. The purpose of this research is to explore the influence of information asymetry, budget adequacy, organizational commitment and environmental uncertaintly to the relationship budgetary participation with budgetary slack.The population in this research is 24 office in local goverment (SKPD) of City Dumai. The sampling design of this research is purposive sampling with the final sample 88 people as a two till four echelon . This research used primary data by dissemination of the questionnaire conducted 24 office local government (SKPD) of City Dumai. Technical analyse for test hypothesis simple linear regression and MRA.The results of this research showed that budgetary participation positively significant influence to budgetary slack. Information asymetry and organizational commitment positively significant influence in relationship budgetary participation to budgetary slack. While budget adequacy and environmental uncertaintly unable to influence relationship budgetary participation to budgetary slack.Keywords: Budgetary Participation, Information Asymetry, Budget Adequacy, Organizational Commitment, Environmental Uncertaintly, Budgetary Slack.